Improving the rheological and tribological properties of emulsion-filled gel by ultrasound-assisted cross-linked myofibrillar protein emulsion: Insight into the simulation of oral processing - Ye Tao; Jiaming Cai; Peng Wang; Lei Zhou; Jiale Chai; Zixu Wang; Xinglian Xu (Ultrasonics Sonochemistry)
This study aimed to investigate the effect of ultrasound-assisted cross-linking of myofibrillar protein (MP) emulsions on the enhancement of rheological and tribological properties of emulsion-filled gel. The micro-morphology, texture, water hold capacity (WHC), chemical forces, linear shear rheological behavior, large amplitude oscillatory shear (LAOS), oil-released content, and simulated oral friction of the water-filled gel (WP-G), the original MP fabricated emulsion-filled gel (NP-G), the crosslinked MP fabricated emulsion-filled gel (NPG-G), and the ultrasound treated crosslinked MP fabricated emulsion-filled gel (NPGU-G) were determined. Results indicated that emulsion as filler phase significantly improved the rheological and tribological properties of the gel, especially for the ultrasound-assisted MP emulsion-filled gel (NPGU-G) group, the smaller droplet size of emulsion contributed to the density and structural uniformity of the gel. Based on the excellent hydrophobic interaction between emulsion droplets and protein matrix, the NPGU-G group presented enhanced hardness, gumminess, chewiness, hydrophobic interaction, creep-recovery behavior, and the retarded transition of nonlinear response. Furthermore, the lower oil-released content and reduced friction coefficient in the NPGU-G group also indicated that the smaller emulsion droplets contributed to the gel quality and mouth lubrication. Consequently, this study demonstrated that ultrasound-assisted cross-linked MP emulsion with smaller droplets can be successfully filled into gel structures, form a denser network structure, and improve the quality of the emulsion-filled gel.